Enhancing customer experience in the service industry : a global perspective - Altinay, Levent; Poudel, Surya (Cambridge Scholars Publishing, 2016)
This book provides a new and definitive overview of customer experience and how it can be managed and enhanced in one of the most dynamic industries in the world-the service industry. Its highly qualified international team of contributors ensures that it adopts a global perspective, and clearly outlines the key theoretical perspectives of customer experience, covering customer experience both from demand and supplier perspectives.Fully informed by the latest research, it explores different country contexts and how they impact upon the customer experience; investigates the social, cultural and.